Comparison of the effectiveness of temporomandibular joint osteoarthritis treatment with corticosteroids, hyaluronic acid, and platelet-rich plasma mono-therapy - I. A. Shynchukovskyi; O. H. Tereshchuk (Сучасні медичні технології)
The prevalence of temporomandibular joint (TMJ) osteoarthritis is 18–85 % of all TMJ dysfunctional conditions. Most patients are elderly, especially women. Today, intra-articular injections are often used for treatment, so it is necessary to study the effectiveness of drug administration on the course of the disease. The number of studies on the effectiveness of certain drugs most commonly used to treat TMJ osteoarthritis is limited, that does not allow correct treatment planning in each individual case.